PENGARUH RANSUM YANG DI HIDROLISIS MENGGUNAKAN ENZIM SELULASE DAN MANNANASE TERHADAP BOBOT KARKAS PADA AYAM BROILER - M. Mairizal; Y. Yusrizal; M. Anung Hidayat (Jurnal Sain Peternakan Indonesia, 2023)
This research aims to determine the effect of palm kernel cake-based diets hydrolyzed using cellulase and mannanase enzymes on carcass weight in broiler chickens. This research used 200 DOC heads produced by PT. Japfa was kept for 35 days in the Poultry Experiment Cage of the Animal Cultivation Laboratory, Faculty of Animal Husbandry, Jambi University. This research used a Completely Randomized Design (CRD) with five treatments and four replications. The variables observed in this research were feed consumption, slaughter weight, absolute carcass weight, and relative carcass weight. Data were analyzed using analysis of variance (ANOVA). If there was a significant effect, then continue with the Duncan test. The results of the study showed that giving rations based on palm kernel cake, which was hydrolyzed using cellulase and mannanase enzymes, had a significant effect (P<0.05) on feed consumption, slaughter weight and absolute carcass weight but had no significant effect (P>0.05) on body weight. Relative carcass. It was concluded that the 50 mL/Kg cellulase enzyme and 100 mL/Kg mannanase enzyme showed increased broiler chicken carcass weight.